Tinjauan Literatur tentang Peran Manajemen dalam Meningkatkan Kinerja Koperasi di Indonesia - Januarianto, Tri; Engelberta Vania; Kamsariaty, Kamsariaty; Wulaningratri, Gabrielle; Satriyanto, Muhammad Dwi (Penerbit Goodwood, 2025)
Purpose: This study aims to improve the managerial capacity of cooperatives in Indonesia by conducting a literature review on the role of management in cooperative performance. Methodology/approach: A qualitative approach was applied by collecting and analyzing relevant research from both nationally accredited and internationally reputable journals. The selected literature focuses on cooperative performance, management roles, digital transformation, and strategic challenges in Indonesia. Results/findings: Cooperatives in Indonesia play a strategic role in supporting the national economy. However, they face significant obstacles, including limited human resources, weak internal business processes, and increased competition. The findings show that cooperative performance can be improved through better customer service and more efficient operations. Conclusion: Cooperatives can enhance their competitiveness and long-term sustainability by adopting digital technology and applying effective management strategies. These improvements are crucial for helping cooperatives adapt to a rapidly changing economic environment. Limitations: This study was limited to secondary data obtained from the existing literature. Thus, the applicability of the findings may vary depending on the type and scale of the cooperative, and further empirical validation is recommended. Contribution: This study contributes to the understanding of how cooperatives can improve their managerial quality, strengthen relationships with their members, and adopt innovation to remain relevant. It also offers a foundation for future research on strategies to support cooperative development in Indonesia.